Building brand image through corporate social responsibility Case Study on Mobilis Telecommunication Company - Hadjer BOUAKKAZ; Houari MAARADJ (Dirassat Journal Economic Issue, 2017)
The present research seeks to investigate the impact of corporate social responsibility on building brand image in the telecommunication sector; the concept of corporate social responsibility (CSR) has gained extensive consideration in recent years. Nowadays firms are using CSR to build brand image and to establish long lasting relations with its stakeholders. However, the relationship between brand image and corporate social responsibility has not been sufficiently explored .Acase study of leading Telecommunication Company Mobilis was conducted. Hypotheses were developed and all of them were accepted. Results showed that social responsible activities of a firm enhance the brand image